Say $f,g\colon R^m\to R^n$ are differentiable at $\vec a\in\mathbb R^m$. That means that
$$
\lim_{\vec h\to\vec 0}\frac{f(\vec a+\vec h)-f(\vec a)-Df(\vec a)(\vec h)}{\Vert \vec h\Vert}=\vec 0,
$$
and the same for $g$. Now what I need to show is that $f\cdot g$ has the following derivative: $f(\vec a)Dg(\vec a)+Df(\vec a)f(a)$, so we need to show that
$$
\lim_{\vec h\to\vec 0}\frac{f(\vec a+\vec h)g(\vec a+\vec h)-f(\vec a)g(\vec a)-f(\vec a)Dg(\vec a)(\vec h)-Df(\vec a)(\vec h)g(\vec a)}{\Vert \vec h\Vert}=\vec 0,